Words & phrases under the constitution - Saharay, H. K., 1931-; Saharay, Madhusudan; Chakravarty, Kali Pada, 1913- (Kolkata : Eastern Law House, 2003)
With reference to India
Includes bibliographical references and index
Keywords: Constitutional law -- India; Constitutional law -- India -- Language